2015
DOI: 10.3389/fmicb.2015.00064
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic shifts of bacterioplankton community composition along the Pearl Estuary: the potential impact of hypoxia and nutrients

Abstract: The significance of salinity in shaping bacterial communities dwelling in estuarine areas has been well documented. However, the influences of other environmental factors such as dissolved oxygen and nutrients in determining distribution patterns of both individual taxa and bacterial communities inhabited local estuarine regions remain elusive. Here, bacterioplankton community structures of surface and bottom waters from eight sites along the Pearl Estuary were characterized with 16S rRNA gene pyrosequencing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
78
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 65 publications
(97 reference statements)
20
78
1
2
Order By: Relevance
“…4; see also Table S5 in the supplemental material). In agreement with our findings, many previous studies have shown that pH and the DO concentration are major drivers of microbial community distributions in various ecosystems (22,(81)(82)(83)(84)(85)(86). pH has been described to be a master variable that integrates the physiochemical status of aquatic ecosystems (87).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…4; see also Table S5 in the supplemental material). In agreement with our findings, many previous studies have shown that pH and the DO concentration are major drivers of microbial community distributions in various ecosystems (22,(81)(82)(83)(84)(85)(86). pH has been described to be a master variable that integrates the physiochemical status of aquatic ecosystems (87).…”
Section: Discussionsupporting
confidence: 81%
“…In a study of the bacterioplankton community composition, the relative importance of the NH 4 ϩ , PO 4 3Ϫ , NO 3 Ϫ , and DO concentrations differed at the order level versus the genus level (22). Similarly, Mantel tests revealed that correlations between the prokaryotic community composition and certain parameters (HCO 3 Ϫ and Na ϩ concentrations, temperature, pH) differed at the genus (95%), species (97%), and subspecies (99%) levels (91).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the northern Gulf of Mexico, one of the largest eutrophication-driven hypoxic zones in the world [Diaz, 2001], it is reported that variation in bacterial communities is associated with chemical differences between oxic and hypoxic water conditions [Bristow et al, 2015;Devereux et al, 2015]. Liu et al [2015] also reported that nutrients and bottom water hypoxia significantly affect changes in bacterioplankton communities in the Pearl Estuary.…”
Section: Introductionmentioning
confidence: 99%